Entire Process Simulation of Corrosion due to the Ingress of Chloride Ions and CO2 in Concrete - Xingji Zhu; Zhaozheng Meng; Yang Liu; Longjun Xu; Zaixian Chen (Advances in Materials Science and Engineering)
A comprehensive mathematical model which can simulate the entire corrosion process of reinforcement in concrete is proposed in this paper. The combined effect of carbonation and chloride ingress is also discussed in the mass transport module. Nonuniform corrosion distribution is employed for the study of mechanical damage in concrete. The link of ABAQUS with MATLAB is adopted for the numerical implementation of the developed model. The numerical results of an illustrative example indicate that the depassivation time of reinforcement, corrosion rate and expansion displacement, and cracking pattern of concrete all can be accurately predicted.